Benefit of feeding Urochloa hybrid cultivar ‘Cobra’ on milk production in Tanzania - Mwendia, Solomon W.; Notenbaert, An Maria Omer; Nzogela, Beatus; Mwilawa, Angello (International Center for Tropical Agriculture, 2022)
Animal genetics, management, diseases, feeds and environment affect milk production in cattle. Feed is the most important and when addressed, cattle show immediate responses. In sub-Saharan Africa, livestock productivity is low largely due to use of low-quality crop residues and natural pastures, often poor in key nutrients for animal performance. In an 8-week on-farm feeding trial with farmers’ participation, milk production under farmers’ practice (FP) was compared with the use of improved Urochloa hybrid cultivar ‘Cobra’ hay (Cobra hay) as an intervention (IN). A crossover design with each cow undergoing FP and IN phases was used. For the initial 2 weeks, the experiment followed FP before shifting to 50-50 FP/IN in week 3 and 100% IN in week 4 and 5, followed by 50-50 FP/IN in week six and 100% FP in week 7 and 8. Milk production increased by 15 % under IN and was associated with better feed utilization efficiency of 2 kg DMCobra hay/L of milk. The use of Cobra hay has potential to increase dairy productivity in Tanzania and other similar tropical ecologies and contexts in sub-Saharan Africa